Annales de L'Institute Henri Poincare. Section B, Calcul des probabilities et statistique - Institut Henri Poincaré. (Paris : Gauthier-Villars, 1982)
Print only.
Title from cover.
Keywords: Probabilities -- Periodicals; Mathematical statistics -- Periodicals